Digital occupants – Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister, Dorothee M. (MedienPädagogik)

Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister., D.M. (MedienPädagogik)

Screencasting: Documenting Processuality - Eckel, Julia (Screen-Images. Screenshot, Screencast, In-Game Photography)

The Virus Is Present, Presence Is Virulent: Being Co(m)present With Others in Times of Corona - Eckel, Julia; Linseisen, Elisa (Epidemics and Othering. The Biopolitics of COVID-19 in Historical and Cultural Perspectives)

Identifizierung quantifizierbarer Bewertungsinhalte und -kategorien mittels Text Mining - Kersting, Joschka
Reading between the lines has so far been reserved for humans. The present dissertation addresses this research gap using machine learning methods. Implicit expressions are not comprehensible by computers and cannot be localized in the text. However, many texts arise on interpersonal topics that, unlike commercial evaluation texts, often imply information only by means of longer phrases. Examples are the kindness and the attentiveness of a doctor, which are only paraphrased (“he didn’t even look me in the eye”). The analysis of such data, especially the identification and localization of implicit statements, is a research gap (1). This work uses so-called Aspect-based Sentiment Analysis as a method for this purpose. It remains open how the aspect categories to be extracted can be discovered and thematically delineated based on the data (2). Furthermore, it is not yet explored how a collection of tools should look like, with which implicit phrases can be identified and thus made explicit (3). Last, it is an open question how to correlate the identified phrases from the text data with other data, including the investigation of the relationship between quantitative scores (e.g., school grades) and the thematically related text (4). Based on these research gaps, the research question is posed as follows: Using text mining methods, how can implicit rating content be properly interpreted and thus made explicit before it is automatically categorized and quantified? The uniqueness of this dissertation is based on the automated recognition of implicit linguistic statements alongside explicit statements. These are identified in unstructured text data so that features expressed only in the text can later be compared across data sources, even though they were not included in rating categories such as stars or school grades. German-language physician ratings from websites in three countries serve as the sample domain. The solution approach consists of data creation, a pipeline for text processing and analyses based on this. In the data creation, aspect classes are identified and delineated across platforms and marked in text data. This results in six datasets with over 70,000 annotated sentences and detailed guidelines. The models that were created based on the training data extract and categorize the aspects. In addition, the sentiment polarity and the evaluation weight, i. e., the importance of each phrase, are determined. The models, which are combined in a pipeline, are used in a prototype in the form of a web application. The analyses built on the pipeline quantify the rating contents by linking the obtained information with further data, thus allowing new insights. As a result, a toolbox is provided to identify quantifiable rating content and categories using text mining for a sample domain. This is used to evaluate the approach, which in principle can also be adapted to any other domain.

Towards Comparable Ratings: Quantifying Evaluative Phrases in Physician Reviews - Kersting, Joschka; Geierhos, Michaela (Data Management Technologies and Applications)
We present a concept for quantifying evaluative phrases to later compare rating texts numerically instead of just relying on stars or grades. We achievethis by combining deep learning models in an aspect-based sentiment analysis pipeline along with sentiment weighting, polarity, and correlation analyses that combine deep learning results with metadata. The results provide new insights for the medical field. Our application domain, physician reviews, shows that there are millions of review texts on the Internet that cannot yet be comprehensively analyzed because previous studies have focused on explicit aspects from other domains (e.g., products). We identify, extract, and classify implicit and explicit aspect phrases equally from German-language review texts. To do so, we annotated aspect phrases representing reviews on numerous aspects of a physician, medical practice, or practice staff. We apply the best performing transformer model, XLM-RoBERTa, to a large physician review dataset and correlate the results with existing metadata. As a result, we can show different correlations between the sentiment polarity of certain aspect classes (e.g., friendliness, practice equipment) and physicians’ professions (e.g., surgeon, ophthalmologist). As a result, we have individual numerical scores that contain a variety of information based on deep learning algorithms that extract textual (evaluative) information and metadata from the Web.

Digital Democracy and the Digital Public Sphere - Fuchs, Christian

Zur Kritik der Politischen Ökonomie des Digitalen Kapitalismus: Die Aktualität von Manfred Knoches Beitrag zur Kritik der Politischen Ökonomie der Medien und der Kommunikation - Fuchs, Christian (Eigentum, Medien, Öffentlichkeit: Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft)

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

Digitale Desökonomie: Unproduktivität, Trägheit und Exzess im digitalen Milieu - Althoff, Sebastian

Food - Media - Senses

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Medienästhetik und dann? - Bartz, Christina (Medienkritik und Wirkungsästhetik. Konvergenzen und Zuschreibungen schädlicher und wünschenswerter Rezeptionseffekte von Literatur und Medien seit dem 18. Jahrhundert)

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Facial Recognition in Law Enforcement - Hälterlein, Jens (The Oxford Handbook of the Sociology of Machine Learning)
Abstract This chapter discusses the use of facial recognition technology (FRT) by law enforcement with a special focus on machine learning applications. First, FRT is situated in the larger context of the rise of video surveillance and a shift in Western security culture. The chapter shows how the promise of FRT addresses the problems of video surveillance. Then, it explains how FRT works and how machine learning techniques such as eigenface and convolutional neural networks come into play. Afterward, it explains how the accuracy and effectiveness of FRT are evaluated and why it is important to take the interplay of human operators and FRT systems into account. Finally, several controversies around the police use of FRT are presented and the limits of technological solutions to the problem of bias are demonstrated.

The use of AI in domestic security practices - Hälterlein, Jens (Handbook of Critical Studies of Artificial Intelligence)

ELSA zieht in den Krieg - Zur Rolle der Kritik an autonomen Waffensystemen für deren Legitimationsstrategien - Hälterlein, Jens

#SayTheirNames: Widerständige Medien der Erinnerung rechter Gewalt«, mit Sarah Horn - Degeling, Jasmin (feministische studien: Feministisches Erinnern)

Szenen kritischer Relationalität

Szenen kritischer Relationalität

Infrastructure’s Distribution of Sensibilities: On Counter / Documentation, Attachment, and the Possibility of a Poetics of Infrastructure - Degeling, Jasmin (Infrastructures of Sense|Making – Techniques, Powers, Operations)

Jenny Schrödl, Eike Wittrock (Hg.): Theater* in queerem Alltag und Aktivismus der 1970er und 1980er Jahre - Degeling, Jasmin (MEDIENwissenschaft: Rezensionen | Reviews)

Tech/Imaginations – Introduction - Schulz, Christian; Schröter, Jens (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Tech/Imaginations (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Infrastrukturen der Anerkennung. Eine Theorie sozialer Medienplattformen - Schulz, Christian

Grundlagen der Medienökonomie: Medien, Wirtschaft und Gesellschaft. - Fuchs, Christian

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Chatbot-Enhanced Requirements Resolution for Automated Service Compositions - Kersting, Joschka; Ahmed, Mobeen; Geierhos, Michaela (HCI International 2022 Posters)
This work addresses the automatic resolution of software requirements. In the vision of On-The-Fly Computing, software services should be composed on demand, based solely on natural language input from human users. To enable this, we build a chatbot solution that works with human-in-the-loop support to receive, analyze, correct, and complete their software requirements. The chatbot is equipped with a natural language processing pipeline and a large knowledge base, as well as sophisticated dialogue management skills to enhance the user experience. Previous solutions have focused on analyzing software requirements to point out errors such as vagueness, ambiguity, or incompleteness. Our work shows how apps can collaborate with users to efficiently produce correct requirements. We developed and compared three different chatbot apps that can work with built-in knowledge. We rely on ChatterBot, DialoGPT and Rasa for this purpose. While DialoGPT provides its own knowledge base, Rasa is the best system to combine the text mining and knowledge solutions at our disposal. The evaluation shows that users accept 73% of the suggested answers from Rasa, while they accept only 63% from DialoGPT or even 36% from ChatterBot.
Keywords: On-The-Fly Computing; Chatbot; Knowledge Base

Brave New Kachel-World? Über Zoom-Booming, Datenkontrolle und öffentliche Infrastrukturen - Weber, Jutta (Von Menschen und Maschinen – Mensch-Maschine-Interaktionen in digitalen Kulturen)

Probably Approximately Correct. Epistemologische Grundlagen der Künstlichen Intelligenz - Weber, Jutta (Mensch-Maschine-Interaktion – Konzeptionelle, soziale und ethische Implikationen neuer Mensch-Technik-Verhältnisse)

Editorial: Anschaulichkeit – Wissen. Macht. Alternativen. - Eckel, Julia; Linseisen, Elisa (Rabbit Eye – Zeitschrift für Filmforschung)
Keywords: Anschaulichkeit; Anschauung; Film; Epistemologie audiovisueller Medien; Erklärbarkeit; Anschauen; Sichtbarkeit; Unsichtbarkeit

Rabbit Eye: Anschaulichkeit (Rabbit Eye - Zeitschrift für Filmforschung)

Verschwörungstheorien in der Pandemie - Fuchs, Christian

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

Digital Capitalism. Media, Communication and Society Volume Three - Fuchs, Christian

Digital Fascism. Media, Communication and Society Volume Four - Fuchs, Christian

Foundations of Critical Theory. Media, Communication and Society Volume Two - Fuchs, Christian

Marxism and Identity - Fuchs, Christian (Searching for a Self. Identity in Popular Culture, Media and Society)

Verschwörungstheorien in der Pandemie. Wie über COVID-19 im Internet kommuniziert wird - Fuchs, Christian

交往资本主义：迈向马克思主义交往理论的批判 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences))

数字资本主义和大数据时代的卢卡奇 - Fuchs, Christian (马克思主义与现实 (Marxism & Reality) 年第5期. (shortened article version))

数字、传播与社会主义 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends))

社交媒体中的数字产消劳动：基于资本主义时间范畴的研究 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (4))

H παρακολούθηση των Κοινωνικών Μέσων - Fuchs, Christian (Η νέα ψηφιακή παρακολούθηση. Κείμενα προς τιμήν του Μηνά Σαματά (in Greek, The New Digital Surveillance: A Volume in Honour of Minas Samatas),)

Geburtstage: Manfred Knoche 80 Jahre - Fuchs, Christian (Publizistik)

Journalismus aus marxistischer Perspektive - Fuchs, Christian (Journalismustheorien)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens)

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik. 2. Auflage)

Sichere Räume, reparative Kritik. Überlegungen zum Arbeiten mit verletzendem Material - Shnayien, Mary (Zeitschrift für Medienwissenschaft)
Medienwissenschaftliche Forschung zu tagesaktuellen Themen ist oft damit konfrontiert, große Mengen an antisemitischem, rassistischem, misogynem, verschwörungstheoretischem Material sichten und analysieren zu müssen, dessen Verletzungspotential auch die jeweiligen Forscher_innen negativ affiziert. Der Beitrag fragt nach möglichen Bewältigungsstrategien, mit denen sich zu verletzendem Material forschen lässt, und die eine wirkungsvolle Kritik desselben ermöglichen, ohne als Forscher_in in die vom Material ausgehenden negativen Affekte und Epistemologien verwickelt zu werden.

Lab Books - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

Die unsicheren Kanäle. Negative und queere Sicherheit in Kryptologie und Informatik - Shnayien, Marie-Luise

Resilienz durch Integration freiwilliger Helfer*innen in den Katastrophenschutz: organisationale und (forschungs-)politische Perspektiven - Hälterlein, Jens; Kaufmann, Stefan (Resilienz als Prozess)

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Algorithms as complementary abstractions. Published online first 2022 - Matzner, Tobias (New Media & Society)

Hannah Arendt: Challenges of Plurality - Matzner, Tobias; Robaszkiewicz, Maria

Thomas Nyckel, Isabel Schmiedel, und Florian Sprenger - Shnayien, Marie-Luise; Engemann, Christoph (The Lab Book. Situated Practices in Media Studies)

ROBOTER BAUEN, PROGRAMMIEREN LERNEN, DIGITALE KULTUREN VERSTEHEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über Arduino in medienwissenschaftlicher Lehre und Forschung - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

FORSCHUNG (BE-)SCHREIBEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über medienwissenschaftliche Laborbücher - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

Arduino - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

FORSCHUNG (BE-)SCHREIBEN - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Marie-Luise; Sprenger, Florian (Open Media Studies)

Institutionen der Medienpädagogik. Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik.)

(De)Coding Social Practice in the Field of XAI: Towards a Co-constructive Framework of Explanations and Understanding Between Lay Users and Algorithmic Systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Animation und Mimesis. Zur digitalen Expansion bewegtbildlicher Mimesis und ‚animimetischem‘ Denken - Eckel, Julia (Mimesis Expanded. Die Ausweitung der mimetischen Zone)

Digitalisierte Lernwelten. Neue Herausforderungen für die elterliche Unterstützung bei der Medienkompetenzentwicklung von Heranwachsenden - Teichert, Jeannine; Gerhardts, L.; Richter, L.; Meister, Dorothee M.; Kamin, A.M. (Empirische Pädagogik)

Minds in Motion – Some Basic Thoughts on AI and Animation - Eckel, Julia; Ehrlich, Nea (In: animationstudies 2.0)

animationstudiesblog 2.0 | Theme: AI and Animation

Intelligence In Between – Documenting AI in Animation - Eckel, Julia (animationstudies 2.0)

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Zweierlei Homophilie: Wendy Hui Kyong Chun und Leo Bersani - Althoff, Sebastian (Mimesis Expanded: Die Ausweitung der mimetischen Zone)

Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

Teilen und die mediale Logik des Dabei-seins - Bartz, Christina (Following. Ein Kompendium zu Medien der Gefolgschaft und Prozesse des Folgens)

Technological Expectations and the Making of Europe - Hälterlein, Jens (Science & Technology Studies)
In a case study approach, the paper traces how technological expectations have been influential in the creation of European institutions, R&D programmes and regulatory instruments and how they have contributed to processes of European integration. The first case study shows how the promises of a coming ‘Atomic Age’ have been mobilized to support the foundation of the European Atomic Energy Community and, thus, contributed to European integration in the post-WW2 era. The second case study analyses how the security stream within the EU’s framework programmes for R&D is shaped by the promise of ‘technosecurity’ and enacts the normative claim of the EU’s security integration in the post-Cold War era. The third case study analyses how the EU’s AI strategy and AI act articulates the vision of a ‘human-centric AI’ and how this vision is related to the EU’s current attempt to restore citizens’ trust in times of crisis.
Keywords: History and Philosophy of Science

Theoriepolitiken des Überlebens: Trauerarbeit mit Lauren Berlant - Degeling, Jasmin; Hohmann, Philipp (Texte zur Kunst 126. Trauern. Mourning)

(De)Coding social practice in the field of XAI: Towards a co-constructive framework of explanations and understanding between lay users and algorithmic systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Reziprozität und das alteritäre Dritte – Über die wechselseitigen Verflechtungen von PageRank und sozialen Medien - Schulz, Christian (Behemoth . A Journal on Civilisation)

Mediale Fluidität oder fluide Medialität? Eine kurze Geschichte des Social-Media-Feeds - Schulz, Christian; Allekotte, Ann-Kathrin (Fluide Mediale. Medialität, Materialität und Medienästhetik des Fluiden)

PATTERNS 2022 The Fourteenth International Conferences on Pervasive Patterns and Applications

Well-being in Plastic Surgery: Deep Learning Reveals Patients' Evaluations - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 10th International Conference on Data Science, Technology and Applications (DATA 2021))

Human Language Comprehension in Aspect Phrase Extraction with Importance Weighting - Kersting, Joschka; Geierhos, Michaela (Natural Language Processing and Information Systems)
In this study, we describe a text processing pipeline that transforms user-generated text into structured data. To do this, we train neural and transformer-based models for aspect-based sentiment analysis. As most research deals with explicit aspects from product or service data, we extract and classify implicit and explicit aspect phrases from German-language physician review texts. Patients often rate on the basis of perceived friendliness or competence. The vocabulary is difficult, the topic sensitive, and the data user-generated. The aspect phrases come with various wordings using insertions and are not noun-based, which makes the presented case equally relevant and reality-based. To find complex, indirect aspect phrases, up-to-date deep learning approaches must be combined with supervised training data. We describe three aspect phrase datasets, one of them new, as well as a newly annotated aspect polarity dataset. Alongside this, we build an algorithm to rate the aspect phrase importance. All in all, we train eight transformers on the new raw data domain, compare 54 neural aspect extraction models and, based on this, create eight aspect polarity models for our pipeline. These models are evaluated by using Precision, Recall, and F-Score measures. Finally, we evaluate our aspect phrase importance measure algorithm.

Artificial Intelligence and the Sociotechnical Imaginary: On Skynet, Self-Healing Swarms and Slaughterbots - Weber, Jutta (Drone Imaginaries. The Power of Remote Vision)

From Optimizing Military Operations to Targeting Terrorist Networks: Social Network Analysis in Data-Driven Warfare - Weber, Jutta; Mayer, Katja (Explorations in Digital Cultures)

Human-Machine Learning und Digital Commons - Weber, Jutta (In digitaler Gesellschaft. Neukonfigurationen zwischen Robotern, Algorithmen und Usern)

Auto-Mobilitätsmanagement? Über eine gelebte Vision Zero, repetitive Fortschrittsversprechen und gerechte Mobilität - Weber, Jutta (Autonome Autos. Medien- und kulturwissenschaftliche Perspektiven auf die Zukunft der Mobilität)

Expanding Technosecurity Culture. On Wild Cards, Imagination and Disaster Prevention - Weber, Jutta (Sensing In/Security: Sensors and the Making of Transnational Security Infrastructures)

Artificial Intelligence in the Age of Technoscience - Weber, Jutta (Routledge Social Science Handbook of Artificial Intelligence)

Das Audioviduum. Eine Theoriegeschichte des Menschenmotivs in audiovisuellen Medien - Eckel, Julia

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian